2008
DOI: 10.1002/syn.20608
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of STriatal enriched protein tyrosine phosphatase in mice results in increased ERK1/2 phosphorylation

Abstract: STriatal Enriched protein tyrosine Phosphatase (STEP) is a brain-specific protein that is thought to play a role in synaptic plasticity. This hypothesis is based on previous findings demonstrating a role for STEP in the regulation of the extracellular signal-regulated kinase1/2 (ERK1/2). We have now generated a STEP knockout mouse and investigated the effect of knocking out STEP in the regulation of ERK1/2 activity. Here, we show that the STEP knockout mice are viable and fertile and have no detectable cytoarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
105
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(119 citation statements)
references
References 26 publications
12
105
2
Order By: Relevance
“…To extend these initial findings, we next examined the effect of various concentrations of ethanol (40,80, and 120 mM) on NMDAR EPSCs in STEP KO mice (21). These results show that 80 and 120 mM produced significant inhibition of the NMDAR currents from WT neurons, but none of the ethanol concentrations tested inhibited the NMDAR in STEP KO neurons ( Fig.…”
Section: Blocking Step Substrates Prevents Ethanol Inhibition Of Nmdarmentioning
confidence: 81%
See 2 more Smart Citations
“…To extend these initial findings, we next examined the effect of various concentrations of ethanol (40,80, and 120 mM) on NMDAR EPSCs in STEP KO mice (21). These results show that 80 and 120 mM produced significant inhibition of the NMDAR currents from WT neurons, but none of the ethanol concentrations tested inhibited the NMDAR in STEP KO neurons ( Fig.…”
Section: Blocking Step Substrates Prevents Ethanol Inhibition Of Nmdarmentioning
confidence: 81%
“…STEP C/S completely attenuated the effects of ethanol on NMDAR EPSCs, suggesting STEP activity was required for ethanol inhibition of NMDAR activity. STEP C/S binds to several STEP substrates and some of these substrates may be used by other cell-signaling pathways to regulate NMDAR activity (19,21). Therefore, we next tested the effects of ethanol on hippocampal synaptic NMDAR EPSCs in WT and STEP KO mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings in PTPN7 deficient mice, however, had suggested that KIM-containing PTP impact on MAP kinase cascades might be very subtle (Gronda et al, 2001). Furthermore, pharmacological inhibition (Paul et al, 2003;Valjent et al, 2005) and mouse knock-out studies also proved PTPN5 to be a physiological regulator of MAP kinase cascades (Venkitaramani et al, 2009). Indeed, also Ptprr knock-out mice displayed MAP kinase hyperphosphorylation in relevant tissues (Chirivi et al, 2007).…”
Section: Functionmentioning
confidence: 99%
“…The affinity of the interaction between MAPK and the KIM dictates the selectivity of a MKP for a particular MAPK substrate (63). The KIM domain is also found in two tyrosine-specific PTPs, the striatalenriched PTP (STEP) and the hematopoietic PTP (HePTP), both of which are capable of dephosphorylating Erk (27,72). Again, in this instance, the KIM domain provides these tyrosine-specific PTPs with MAPK binding specificity and, hence, MAPK substrate selection.…”
mentioning
confidence: 99%